Deforestasi Dan Tanggung Jawab Manusia Dalam Al-Qur’an (Studi Tafsir Hidayatul Insan Karya Abu Yahya Marwan Bin Musa) - yusman, dinda febriana; Ghozali, Abdul Malik; Hendro, Beko (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2024)
This article aims to analyze Abu Yahya Marwan bin Musa's views on deforestation and human responsibility towards the environment in the Qur'an. This research was prepared using qualitative methods with library research techniques, namely by collecting various references related to the research problem, then in analyzing the data the researcher used a content analysis approach. The results of this research include: First, Abu Yahya argues that deforestation as a form of environmental damage is an act of sin that damages the earth. This environmental damage is caused by weak faith, as well as wicked and sinful acts. Secondly, Abu Yahya argues that humans have roles and responsibilities as servants of Allah to worship Him and as caliphs in charge of managing and prospering the earth, and enforcing His commands.